Design, synthesis, molecular docking and anticancer activity evaluation of methyl salicylate based thiazoles as PTP1B inhibitors - Dominika Kołodziej-Sobczak; Łukasz Sobczak; Wojciech Płaziński; Adrianna Sławińska-Brych; Magdalena Mizerska-Kowalska; Klaudia Hołub; Barbara Zdzisińska; Karol Jaroch; Barbara Bojko; Krzysztof Z. Łączkowski (Scientific Reports)
Abstract This work presents a rational synthesis of 14 innovative methyl salicylate based thiazole (MSBT) derivatives, designed as protein tyrosine phosphatase 1B (PTP1B) inhibitors with potent anticancer activity. Enzyme inhibition studies were performed for all compounds. In addition, molecular docking simulations and assessment of antiproliferative activity were performed for the most active of the lot. For antiproliferative studies, the cell lines of breast cancer (T47D) and non-small-cell lung carcinoma (A549), as well as healthy control of human skin fibroblasts (HSF), were used. As a result, 3 compounds were found to inhibit the PTP1B enzyme in submicromolar concentrations: 3j (IC50 = 0.51 ± 0.15 µM), 3f. (IC50 = 0.66 ± 0.38 µM) and 3d (IC50 = 0.93 ± 0.51 µM), all surpassing the reference inhibitor as much as sixfold (IC50 = 3.23 ± 0.85 µM). Moreover, compound 3j was found to be highly selective towards T47D cancer cells. The cellular mechanism of compound 3j action was associated with the inhibition of DNA replication via blocking the S phase of interphase and induction of apoptosis. Also, molecular docking simulations made for compound 3j revealed continuous interactions between the molecule and the catalytic site, as well as with all the loops involved in the catalytic activity of the protein. Therefore, the new group of MSBT derivatives offers great promise for safe and effective anticancer therapy.